AI in Health Insurance: Transforming Member Enrollment and Personalization - Gowtham Chilakapati (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative role of artificial intelligence in revolutionizing health insurance enrollment and personalization processes. The article employs a mixed-methods approach combining quantitative analysis of implementation metrics from insurance providers with qualitative assessment through stakeholder interviews and case studies. The article identifies key success factors for effective AI implementation, quantifies operational efficiencies, assesses improvements in member experience, and explores challenges, including data privacy concerns, algorithmic bias, regulatory compliance issues, technical implementation barriers, and user adoption hurdles. The article reveals that strategic AI implementation significantly reduces enrollment processing times, decreases administrative costs, improves customer satisfaction, and provides a compelling return on investment. The article highlights emerging best practices for personalization strategies and presents recommendations for insurers at different stages of AI maturity. By identifying effective implementation strategies, this work contributes valuable insights to guide insurance providers toward successful AI transformations that ultimately improve healthcare accessibility and affordability for consumers.